Resistance of peanut varieties to phytoplasm. Recently, witches' broom disease on peanut is becoming more important in Indonesia The use of resistant varieties is very potential to overcome the yield loss caused by the disease. Ten peanut varieties were evaluated for their response to phytoplasma using insect vector transmission. Three categories of plant response were observed during the experiment, i.e. moderate resistant (var, Macan, Zebra, and Simpai), susceptible (var. Biawak, Treggili - Sandi Nugroho; Rusmilah Suseno; Sri Hendrastuti Hidayati; Purnama Hidayat (Buletin Hama dan Penyakit Tumbuhan, 2000)
Resistance of peanut varieties to phytoplasm. Recently, witches' broom disease on peanut is becoming more important in Indonesia The use of resistant varieties is very potential to overcome the yield loss caused by the disease. Ten peanut varieties were evaluated for their response to phytoplasma using insect vector transmission. Three categories of plant response were observed during the experiment, i.e. moderate resistant (var, Macan, Zebra, and Simpai), susceptible (var. Biawak, Treggiling, Pelanduk, and Kidang), very susceptible (var. Gajah, Tupai, and Banteng). The average seed weight decrease per plant due to the phytoplasma infection was 40.99 - 100%.